Model Bisnis Dan Antarmuka Pelanggan E-Commerce Pada PT. SMG - Rudy, Rudy; W., Anita P.; O., Anita; Octaffany, Octaffany (Bina Nusantara University, 2011)
PT. SMG is a company which sells music and movies product in CDs, VCDs and DVDs. PT. SMG relies its business on direct selling through its outlets. PT. SMG needs a solution to facilitate the customers’ needs in getting product information and online transactions. E-commerce can be use to develop business and provide an alternative solution to customers on how to transact and obtain product information from PT. SMG using the internet. The objective of this study is to design a business model and customer interface of e-commerce website for PT. SMG. The methodology uses e-commerce business model and customer interface design by Rayport and Jaworski. The website interface design uses a 7C framework approach: Context, Content, Communication, Commerce, Connection, Community and Customization. The result achieved is an e-commerce website that helps sales system and enhances the company competitiveness. The conclusions obtained are that PT. SMG can take advantage of e-commerce to support their sales system and the business model online for PT. SMG is the widest-assortment model.